Modelling the costs of constraining the transition to renewable energy in South Africa - Merven, Bruno; Hartley, Faaiqa; Robinson, Sherman; Arndt, Channing (United Nations University, 2020)
For decades cheaper and easily available fossil fuels have underpinned the energy system of South Africa and inhibited the potential for achieving a sustainable low carbon economy. Favourable developments in renewable energy technologies and falling prices provide an opportunity for the country to reduce its emissions significantly without sacrificing economic development. This paper assesses the technical potential for expanded use of renewable technologies in electricity production and the economic impact of a transition to renewable energy in South Africa. The paper compares two possible energy pathways for the country, both of which respect South Africa’s aggregate emissions commitments under the Paris Accord. In one scenario, investment in renewable technologies is constrained and, in another, it is not. Our findings show that, under the unconstrained investment scenario, renewable energy technologies would become the largest least-cost contributor to electricity generation in the country over the next two decades. At the national level the shift to renewable energy would have a net positive impact on real GDP and employment, with gains shared widely across the economy. Under both scenarios, there is a decline in coal mining that requires policy attention to mitigate the negative impacts on employment and regional incomes.